Differential diagnosis for the dermatologist - Jackson, Scott M. (Springer Berlin Heidelberg, 2012)
When faced with a challenging dermatologic problem, physicians are often required to perform a time-consuming search through large dermatologic texts in order to find information that will assist in the necessary differential diagnosis. This comprehensive and concise handbook is designed to simplify this process dramatically, permitting rapid identification of the correct diagnosis. Hundreds of dermatologic diagnoses, morphologic features, drug-induced disorders, extracutaneous manifestations, histologic findings, and random other findings are listed in alphabetical order and in a homogeneous, reader-friendly structure. The differential diagnoses are shown under each main diagnosis, sorted according to similarity with that diagnosis. Since the first edition, approaching 50 new diagnoses have been added, and many new images included. In addition, a quick list of treatment options is now included for each diagnosis. This easily portable book will be of great value for dermatologists and all who deal with dermatologic diseases.